2016
DOI: 10.1017/s0967199415000623
|View full text |Cite
|
Sign up to set email alerts
|

Individual differences in the distribution of sperm acrosome-associated 1 proteins among male patients of infertile couples; their possible impact on outcomes of conventional in vitro fertilization

Abstract: The aims of this study were to show the existence of individual differences in the distribution of sperm acrosome-associated 1 (SPACA1) among male patients of infertile couples and to examine their possible impact on the outcomes of conventional in vitro fertilization (IVF). The spermatozoa were collected from male patients of infertile couples, washed by centrifugation, collected by the swim-up method, and then used for clinical treatments of conventional IVF. The surplus sperm samples were fixed and stained … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 22 publications
0
11
0
Order By: Relevance
“…It has been reported that ASA or other sperm antigen inhibitors could influence fertilisation process through at least one of four ways: (1) blocking gamete fusion, (2) preventing sperm-zona pellucida binding and penetration, (3) inhibiting acrosome reaction or (4) immobilising sperm [31][32][33][34][35][36][37][38][39][40][41][42][43][44][45][46][47][48].…”
Section: Novel Immune-contraceptive Methods and The Discovery Of Asamentioning
confidence: 99%
“…It has been reported that ASA or other sperm antigen inhibitors could influence fertilisation process through at least one of four ways: (1) blocking gamete fusion, (2) preventing sperm-zona pellucida binding and penetration, (3) inhibiting acrosome reaction or (4) immobilising sperm [31][32][33][34][35][36][37][38][39][40][41][42][43][44][45][46][47][48].…”
Section: Novel Immune-contraceptive Methods and The Discovery Of Asamentioning
confidence: 99%
“…A, Tyrosine‐phosphorylated proteins (green fluorescence) and SPACA 1 proteins (red fluorescence) were detected in the cauda epididymal spermatozoa by double immunostaining (a representative of six replicates). The cauda epididymal spermatozoa were washed with a phosphate‐buffered saline that contained polyvinyl alcohol ( PBS ‐ PVA ) three times, treated with mouse anti‐phosphotyrosine ( pY ) monoclonal antibody or guinea pig anti‐ SPACA 1 polyclonal antibody, and subsequently with fluorescein isothiocyanate‐conjugated or tetramethylrhodamine‐conjugated secondary antibodies, as described previously 25, 56. An arrow indicates the distribution of the acrosomal tyrosine‐phosphorylated proteins in the equatorial subsegment.…”
Section: Acrosomal Proteinsmentioning
confidence: 99%
“…According to investigations of human spermatozoa from infertile patients,56 human SPACA1 proteins might not be tyrosine‐phosphorylated, unlike bovine SPACA1 proteins. However, their distribution patterns in the acrosomal principal segment are varied among human spermatozoa, as with bovine SPACA1 proteins, and could be classified into three grades.…”
Section: Acrosomal Proteinsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the acrosome 375 membrane (internal and external membranes), the sperm acrosome membrane-associated family 376 (i.e., SPACA3, SPACA1, and SPACA4) [63,64] are sperm surface membrane proteins that may be 377 involved in the adhesion and fusion of the sperm to the egg prior to fertilization [65]. SPACA1 and 378 SPACA3 are localized in the acrosomal matrix, including the principal segment and equatorial 379 segment, and are proteins characterized as membrane antigens [63,65,66]. SPACA1 may be 380 involved in sperm fusion with the oölemma, since treatment of human sperm with the anti-SPACA1 381 antibody prevented sperm penetration into zona-free hamster eggs [63].…”
mentioning
confidence: 99%